Analysis of Drinking Water Quality for Presence of Heavy Metals and Its Impacts on Health of Local Population in Sibi District - Uzma, Imran; Chandio, Tasawar A. (European Journal of Sustainable Development, 2017)
This study aimed at finding out the presence of heavy metals in the drinking water sources of Sibi District, Pakistan. These metals are causing various diseases in the local population such as browning of the teeth, bone deformations, and malfunctioning of different organs of the human body. The researchers collected water samples from 8 sampling sites of Sibi district and the same were analyzed for fluoride, lead, arsenic and manganese. Modern instruments available in the advanced GSP laboratory were used for examining these samples. The results showed that the values of pH and TDS in water samples ranged from 7.2 to 8.31 and 650 to 9,800, fluoride was present from 2.0 to 12.5 mg/l, arsenic values were observed in the range of 0.0008 to 4.56 mg/l and lead was present from 0.0001 to 0.02 mg/l and manganese was present from 0.002 to 0.353 mg/l. These results show that the values of heavy metals are mostly higher than the values set by World Health Organization (WHO) except values of Manganese and Lead which were mostly within permissible limits. The reason for the presence of these heavy metals was observed to be the combination of rock alterations and exploitation of surface and underground minerals in the selected areas of Sibi district.